2015
DOI: 10.25011/cim.v38i1.22577
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Following Treatment of Trochanteric Fractures with Proximal Femoral Nail versus Cementless Bipolar Hemiarthroplasty in Elderly

Abstract: Purpose: There is currently no gold standard treatment for unstable intertrochanteric fractures of the elderly. Internal fixation and hemiarthroplasty are two common treatment methods but studies comparing the functional outcomes of these procedures in the elderly are limited. This study evaluates the functional outcomes of hip fracture patients treated either with internal fixation or hemiarthroplasty. Methods: Eighty-six elderly (>60 years) patients who presented with isolated, unstable inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 44 publications
4
49
0
1
Order By: Relevance
“…3). However, the result of sensitive analysis by excluding the outlier study [11] did not alter significance, suggesting the result reliable.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…3). However, the result of sensitive analysis by excluding the outlier study [11] did not alter significance, suggesting the result reliable.…”
Section: Resultsmentioning
confidence: 95%
“…The quality of the RCTs was acceptable, all the RCTs had reported their methods of randomization. Two RCTs [10,11] were conducted through the computer-generated list, and the remaining through a sealed opaque equivalent envelope. [12] None of the included RCTs reported blinding of the surgeons, participants, or assessors, though 1 study mentioned that the randomization list was concealed from the surgeon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow‐up time ranged from 3 to 48 months. A comprehensive characteristic of the trials included in this meta‐analysis were reported in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 774 IF and 814 AR cases with ITFs in the elderly from 14 studies were included. Seven studies were from the Asia (China Chang,Shen,Tang,Yang , South Korea Kim,Kim,Park ), [25][26][27][28][29][30][31] 6 studies were from the Europe (Turkey Kayali, Görmeli, Desteli, Özkayın, Güven , France Bonnevialle ), [32][33][34][35][36][37] and 1 study was from Africa Gashi . 38 Among these eligible trials, the AR included hemiarthroplasty and total hip arthroplasty, the IF included intramedullary system (GN, PFN, PFNA, IN) and extramedullary system (CHS, DHS), which represented the commonly used implants in clinical practice.…”
Section: Literature Searchmentioning
confidence: 99%